2014
DOI: 10.1016/j.celrep.2014.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Regulation by AUTS2 in Neuronal Migration and Neuritogenesis

Abstract: Mutations in the Autism susceptibility candidate 2 gene (AUTS2), whose protein is believed to act in neuronal cell nuclei, have been associated with multiple psychiatric illnesses, including autism spectrum disorders, intellectual disability, and schizophrenia. Here we show that cytoplasmic AUTS2 is involved in the regulation of the cytoskeleton and neural development. Immunohistochemistry and fractionation studies show that AUTS2 localizes not only in nuclei, but also in the cytoplasm, including in the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
200
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(216 citation statements)
references
References 36 publications
12
200
2
2
Order By: Relevance
“…Indeed, it has been described as a locus that confers risk across neurodevelopmental diagnostic boundaries4680. The functions of the AUTS2 protein are largely unknown but it has been suggested to play a role in cytoskeletal regulation81. The STARD9 gene encodes a mitotic kinesin which functions in spindle pole assembly82.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been described as a locus that confers risk across neurodevelopmental diagnostic boundaries4680. The functions of the AUTS2 protein are largely unknown but it has been suggested to play a role in cytoskeletal regulation81. The STARD9 gene encodes a mitotic kinesin which functions in spindle pole assembly82.…”
Section: Discussionmentioning
confidence: 99%
“…The faint extension creases and mild contractures of the fingers are both likely to be caused by the aberrant fetal development, primarily caused by the AUTS2 defect or secondary through lack of movement in utero caused by the AUTS2 defect 24. As AUTS2 is highly expressed in the developing brain and the functional clues at the molecular and protein level so far also indicate an important role in neuron development, one could hypothesise that diminished movements in utero (for neurological reasons) are causing these defects 1 3 4 5. However, embryological studies did show more evidence for the theory that the same genetic factors are responsible for flexion crease formation as well as development for joint movement.…”
Section: Discussionmentioning
confidence: 99%
“…AUTS2 activates gene expression in the central nervous system by binding to the polycomb repressive complex 1.5 (that normally suppresses gene transcription by chromatin remodelling) 4. The full-length AUTS2 transcript is located in the cytoplasm and in the nucleus, whereas the shorter transcript starting in exon 9 is only located in the nucleus 2 5. The cytoplasmic AUTS2 is important in cytoskeletal regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has confirmed that the extra ROS produced during neural oxidative stress could alter the arrangement of neuronal cytoskeleton 4, 5. Since the cytoskeleton plays crucial roles in a variety of neuronal physiological processes, including organelle and vesicular trafficking, maintenance of basic architecture and polarity, neuritogenesis and migration 6-9. It is acknowledged that the cytoskeletal dysfunction has been implicated as an underlying cause of neuronal apoptosis, and even cell death in CNS diseases 10.…”
Section: Introductionmentioning
confidence: 99%